Enhanced hydrogen generation from biodiesel-waste glycerol using Ni/SBA-15 catalyst synthesized from boiler ash - Nornasuha, Abdullah; Nurul Aini, Razali; Herma Dina, Setiabudi; Abdul Rahman, Mohamed; Aishah, Abdul Jalil (Elsevier Ltd, 2024)
The successful synthesis of the mesostructured SBA-15 derived from extracted boiler ash silica (BA) with distinct Ni loading (15 wt%, 20 wt%, and 25 wt%) towards H2 production from CO2 and C3H8O3 was explored. The catalysts prepared by the ultrasonic-assisted method were subjected to 8 h of GDR at 800 °C. The XRD and N2 sorption revealed reduced area and crystallinity in 25 wt% Ni versus 15 wt% Ni catalyst. 20 Ni/SBA-15(BA) exhibited a larger area (234 m2/g), aperture (8.99 nm), and small NiO crystallite (18.34 nm), implying well-dispersed Ni species on SBA-15(BA) surface. 20 Ni/SBA-15(BA) displayed the highest GDR catalytic activity (57 %), credited to its accessible structure, strong Ni–O–Si bonding, and good Ni dispersion that reduced coke formation (9.8 % carbon). This discovery highlights the excellent performance of 20 wt% of Ni loaded on SBA-15 by using green silica source extracted from waste material for H2 fuel production.